The Civil War Confiscation Acts : failing to reconstruct the South - Syrett, John, 1942- (Reconstructing America (Series), 2005)
This is an account of two significant laws passed during the US Civil War, The Confiscation Acts (1861-62). It examines the political contexts, especially the debates in Congress, and how the failure of the Confiscation Acts during the war presaged the political and structural shortcomings of Reconstruction afterwards.